Proses dan prinsip pertanggung-jawaban pengangkutan barang melalui laut berdasarkan Undang-Undang Nomor 17 Tahun 2008 - Febrianti, Wenita; Nabila, Rovi Ayu (Maliki Interdisciplinary Journal, 2024)
Transporting goods by sea is an important part of efforts to advance the Indonesian economy as a maritime country. This is because transporting goods by sea has advantages compared to transporting goods or people by land and air, including lower costs and being able to carry a larger number of passengers or goods. However, transporting goods by sea carries quite high risks in the process of loading, delivering/shipping and unloading goods, including the risk of loss, damage or loss. In order to protect the parties involved in sea transportation activities, the government regulates legal regulations regarding shipping in Law Number 17 of 2008. The research method used in this article is the literature study research method. The data obtained from the literature study was then analyzed descriptively to obtain an overview of the process and principles of responsibility for transporting goods by sea based on the Laws of the Republic of Indonesia. The importance of understanding the principles and responsibilities of transporting goods by sea aims to protect consumers and sea transport service providers if undesirable things happen during the process of transporting goods by sea.